The impact of SNAP-Ed interventions on California students' diet and physical activity during COVID-19 - Amanda Linares; Kaela Plank; Sridharshi C Hewawitharana; Gail Woodward-Lopez (Cambridge University Press, 2023)
Abstract Objective: School-based CalFresh Healthy Living (CFHL) (California's SNAP-Ed) interventions adapted to new learning environments necessitated by COVID-19. We examined the impact of these interventions on student diet and physical activity (PA) outcomes. Design: Quasi-experimental, two-group, pre-post. Setting: California public schools with ≥50 % of students Free and Reduced Price Meal-eligible (n intervention = 47; n comparison = 17). Participants: Fourth- and fifth-grade students who completed the online Eating and Activity Tool for Students at pre and post (n intervention = 1087; n comparison = 846 students). Results: Intervention students reported a significantly greater increase in consumption frequency of total fruit (by 0·16 times/d; P = 0·032), driven primarily by a greater increase in 100 % fruit juice (by 0·11 times/d; P = 0·007). Intervention students reported a significantly greater increase in total vegetable consumption frequency (by 0·45 times/d; P < 0·001) than comparison students. Specifically, intervention students reported increased, whereas comparison students reported decreased, consumption frequencies for starchy vegetables (0·05 v. −0·10 times/d, P < 0·001), salad/green vegetables (0·01 v. −0·11 times/d, P = 0·005) and beans (0·04 v. −0·03 times/d, P = 0·025). Consumption frequency of other vegetables decreased in both groups (−0·01 v. −0·09 times/d) but decreased more among comparison students (P = 0·048). No differences in pre-post change in PA outcomes were detected. Conclusions: Findings suggest that despite COVID-19-related challenges necessitating programme modifications, CFHL interventions played a role in protecting student consumption of fruit and vegetables during the 2020-2021 school year. Therefore, it appears that school-based CFHL interventions can be a viable means of safeguarding student nutrition at a time when access to nutritious food and PA opportunities are hindered.